PENGARUH HARGA DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN UNTUK MENGINAP PADA HOTEL BHINNEKA DI GRESIK - Susetyorini, Susetyorini; Purwanto, Yosua Budi (Fakultas Ekonomi Universitas Gresik, 2012)
Increasingly ÃƒÆ’Ã‚Â¯Ãƒâ€šÃ‚Â¬Ãƒâ€šÃ‚Âerce competition in the Hospitality industry. Various strategies can be chosen to be implemented by the managers of hotels in order to compete and continue to grow in line with consumer demands. Understand the hotel is in developing or not developing governance is a step that should always be done. Hotel Bhinneka Gresik pricing policy, which offered relatively cheap prices for the intended market segment is medium. Relatively low prices and satisfactory service is supported, so the company has hopes that consumers have decided to stay at this hotel, and this course meets the basic objectives of the companyÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬ÃƒÂ¢Ã¢â‚¬Å¾Ã‚Â¢s proÃƒÆ’Ã‚Â¯Ãƒâ€šÃ‚Â¬Ãƒâ€šÃ‚Âts.Referring to the fact that researchers interested in conducting research on ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€¦Ã¢â‚¬Å“The InÃƒÆ’Ã‚Â¯Ãƒâ€šÃ‚Â¬ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡uence of Price and Service Satisfaction Of Customer To Stay In Hotel Unity in GresikÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€šÃ‚Â. The purpose of this study were: To determine whether there is signiÃƒÆ’Ã‚Â¯Ãƒâ€šÃ‚Â¬Ãƒâ€šÃ‚Âcant inÃƒÆ’Ã‚Â¯Ãƒâ€šÃ‚Â¬ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡uence between price and service to customer satisfaction Unity Hotel in Gresik.The population of this study is the overall consumer who stay at the Hotel Bhinneka Gresik. Because the population is too much then the pen entuan number of samples using the purposive random sampling using the formula of Nursalam and obtained a sample of 97 people many consumers. The variables in this study consisted of the cost of the service as independent variables and customer satisfaction as the dependent variable. Methods of data collection using questionnaires. Analysis of data using multiple regression analysis.